SUPERVISORS' ASSESSMENT OF MODERN OFFICE TECHNOLOGY COMPETENCIES EXPECTED OF OFFICE TECHNOLOGY AND MANAGEMENT (OTM) GRADUATE WORKERS IN DELTA STATE (NAU Journal of Technology and Vocational Education, 2024)
This study was carried out to determine the modern office technology competencies expected of officetechnology and management (OTM) graduate workers by supervisors in Delta State. The study wasguided by two research questions and two hypotheses tested at 0.05 level of significance. Therespondents consisted of 142 supervisors, made up of 74 heads of department and directors ofgovernment establishments, and 68 managers and directors of private establishments in the study area.Survey research design was used to conduct the study. A 28-items questionnaire was used to collectdata from respondents, which was used for the research. The instrument was validated by experts andhad a total Cronbach Alpha reliability coefficient of 0.77. Mean and standard deviations were used toanswer the research questions, while t-test was used to test the null hypotheses. The findings of thestudy indicated that the supervisors, who are employers as well, very much expect informationprocessing competencies from the OTM graduate workers. The extent of supervisors' expectations ofinformation processing competencies did not differ significantly based on the mean ratings of male andfemale supervisors of OTM graduates in government and private establishments. The findings alsoreveal that supervisors expect much communication competencies from the OTM graduate workers.The extent of supervisors' expectations of communication competencies did not differ significantlybased on the mean ratings of experienced and inexperienced supervisors of OTM graduate workers ingovernment and private establishments. The findings imply that various modern office technologycompetencies are much needed in government and private establishments irrespective of experienceand gender of the supervisors. Hence, the identified competencies need to be emphasized in curriculumpractice, training and development for future office technology and management workers. Based onthe findings and the implications, it was recommended among other things that, curriculum planners,business and OTM education lecturers should ensure that the competencies required for modern officetechnologies are entrenched in the school curriculum and taught in the institutions